Effects of mixing tallow methyl ester with diesel fuel on the thermal characteristics of diesel engine - Mohamed F. Al-Dawody; Duraid F. Maki; Wisam Al-Obaidi; Emad D. Aboud; Khaled Al-Farhany; Ammar Abdulkadhim; Tikendra Nath Verma; Wasim Jamshed; Assmaa Abd-Elmonem; Neissrien Alhubieshi; Fayza Abdel Aziz ElSeabee; Hijaz Ahmad (Energy Conversion and Management: X)
The purpose of the current study is to evaluate the impact of using beef Tallow methyl ester blends on the thermal parameters of diesel engine numerically utilizing Diesel-RK simulation software. The multizone combustion model is used and the governing equations are solved for each independent zone. The engine characteristics were examined under three different volumetric blends of Tallow methyl ester (10 %, 20 % and 30 %) in addition to plain diesel case for comparison. The obtained results showed slight reduction in pressure, heat release for all blends of Tallow methyl ester with respect to diesel fuel alone. The Sauter mean diameter of the droplets was increased by 1.68 %, 3.34 % and 5 % for 10 %, 20 % and 30 % Tallow methyl ester respectively. The higher tallow methyl ester ‘s cetane number is responsible for shorter ignition delay which in turn makes the combustion starts earlier. The brake specific fuel consumption increased 1.68 %, 3.34 % and 5 % for 10 %, 20 % and 30 % Tallow methyl ester respectively due to the difference of density, viscosity and energy contents. Noticeable reduction in the Bosch Smoke Number as the use of 20 % TME and 30 % Tallow methyl ester reported reduction of 13.25 % and 17.8 % while the Particulate Matter is dropped significantly by 11.1 %, 12.9 %, 18.4 % correspond to 10 %, 20 %, and 30 % percentages of Tallow methyl ester biodiesel. The plenty of oxygen quantity in Tallow methyl ester biodiesel leads to emit more Nitrogen oxides relative to diesel. Base on the results obtained, 20 % TME is best compromised blend that can recommended to be used in diesel engine without any modification of the engine. The current findings matched well with the different scientists’ results.